2023
DOI: 10.1002/adom.202202717
|View full text |Cite
|
Sign up to set email alerts
|

Vertically‐Stacked Discrete Plasmonic Meta‐Gratings for Broadband Space‐Variant Metasurfaces

Abstract: Reexamining the plasmonic metasurfaces for efficient transmissive nanophotonics devices has recently drawn considerable attention. It attributes to their ease of fabrication and tunability in terms of the excitation of abundant multipoles. Despite recent efforts in developing plasmonic meta‐atoms, meta‐gratings provide an ultimate solution that enables efficient conversion of the polarization in a broadband range, particularly at optical frequencies. In this work, by vertically stacking meta‐gratings whose ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Specifically, the efficiencies of Gaussian and donut focusing modes are 38.6% and 36.1%, respectively. The working efficiency can be effectively improved by introducing a toroidal response, [ 23 ] employing an inverse design approach, [ 24 ] and optimizing the fabrication process.…”
Section: Metalens Design and Characterizationmentioning
confidence: 99%
“…Specifically, the efficiencies of Gaussian and donut focusing modes are 38.6% and 36.1%, respectively. The working efficiency can be effectively improved by introducing a toroidal response, [ 23 ] employing an inverse design approach, [ 24 ] and optimizing the fabrication process.…”
Section: Metalens Design and Characterizationmentioning
confidence: 99%
“…For this purpose, we have conducted a theoretical analysis based on multipole decomposition method developed for light scattering 76 78 In this method, the total electric fields over the resonators composing the metasurface induced by the incident light are calculated, and then the multipole moments of the resonators are extracted following their definition, 79 , 80 in which the current density is replaced by the induced polarization vector. The detailed formulation regarding the computation of the multipole moments is indicated in Sec.…”
Section: Ultrahigh Q-factor Resonant All-dielectric Metasurfacementioning
confidence: 99%
“…For example, Shen et al demonstrated a metasurface with plasmonic nanogap cavities, utilizing deep-subwavelength cavities with embedded diamond slabs to get a higher nonlinear frequency conversion efficiency [28]. However, such centrosymmetric polarizationindependent metasurfaces are facing difficulties in exciting anisotropic responses, grating metasurfaces provide a solution to polarization-dependent responses [29][30][31]. Chen et al achieved a high reflection anisotropy by a graphene-metal grating metasurface [31].…”
Section: Introductionmentioning
confidence: 99%